The development of the system of individual tenure for Africans: with special reference to the Glen Grey Act, c1894-1922 - Ally, Russell Thomas (Rhodes University, Faculty of Humanities, Department of History, 1985)
The Glen Grey Act was promulgated in August 1894. The main provisions of the Act were for the survey into individual allotments of land held tribally and for a system of local self-government. Described by its originator, C.J. Rhodes, as a 'Bill for Africa, it was first applied to the district of Glen Grey and subsequently extended (in a piece-meal fashion) to a number of districts in the Transkei. The Act was introduced at a crucial stage in South Africa's history. During this period the country stood poised on the threshhold of a significant and far-reaching transformation. The South Africa of 'old', predominantly agricultural and rural was giving way to a 'new' South Africa, modern and industrial. At the centre of this development was the mineral discoveries of the 1860s and 1880s. The period of colonial conquest had also virtually been completed. Most of the hitherto independent African chiefdoms had either been broken up or were under European control. The most urgent problem which now faced the new rulers was devising a policy to govern the millions of black people over whom they had assumed responsibility. Of crucial concern was the creation of working class to minister to the needs of the developing economy. This task was made all the more difficult by the divisions which existed among the ruling groups at the time. To all intents and purposes the country was made up of essentially four independent and autonomous regions. Although the economic changes which were taking place would hasten the unification of the country, until that happened it was well-nigh impossible for a uniform 'native policy' to take shape. The inevitable consequence was the emergence of a number of regional responses to what was essentially a country-wide issue. As the unification of South Africa drew closer however these different regional responses began to vie with each other for supremacy at a national level. The Glen Grey policy then was the response of the Cape to the changes which were taking place in the country. As such, it drew much of its inspiration from the traditions which had developed in the Cape Colony. Its initiators did not however view it as only a regional policy. For them it had applicability to the whole country. It was therefore to be expected that they would attempt to 'sell' their policy to the rest of the country. In the end however it won few adherents outside of the Cape Colony and when Union became an established fact it bowed out to a policy favoured largely by the northern provinces. To be sure the Glen Grey system did linger on for a while in those districts where it had first been applied but it would not be long before it was to fall into official disapproval. While the Glen Grey Act was ushered in with much fanfare and vaunted expectations, its demise was silent and ignominous. The grandiose course which it had charted for the taking-in-hand of the 'native question' came to naught, as did the profound and far-reaching changes which it was believed the policy would inaugurate. The origins of this policy, its implementation and actual working, and the reasons why in the end it foundered and was abandoned will be the main themes of this thesis.
Keywords: Cape of Good Hope (South Africa) -- History; Labor policy -- South Africa -- History; Black people -- Employment -- South Africa -- History; South Africa -- Politics and government -- History